2008
DOI: 10.4049/jimmunol.181.6.4389
|View full text |Cite
|
Sign up to set email alerts
|

Lung Resident Mesenchymal Stem Cells Isolated from Human Lung Allografts Inhibit T Cell Proliferation via a Soluble Mediator

Abstract: Development of allograft rejection continues to be the major determinant of morbidity and mortality post-lung transplantation. We have recently demonstrated that a population of donor-derived mesenchymal stem cells are present in human lung allografts and can be isolated and expanded ex vivo. In this study, we investigated the impact of lung resident mesenchymal stem cells (LR-MSCs), derived from allografts of human lung transplant recipients, on T cell activation in vitro. Similar to bone marrow derived MSCs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
154
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 186 publications
(160 citation statements)
references
References 40 publications
5
154
0
1
Order By: Relevance
“…34,35 MSCs, including LR-MSCs, demonstrate an in vitro potential to inhibit T-cell function via secretion of soluble mediators, such as prostaglandin E 2 . 16,36 However, MSCs potentiate fibrotic differentiation of other mesenchymal cells by secreting profibrotic mediators, such as TGF-␤1. 37 Thus, although MSCs can likely modulate an inflammatory microenvironment, they can also promote fibrogenesis by secreting profibrotic mediators 37 or differentiating to myofibroblasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34,35 MSCs, including LR-MSCs, demonstrate an in vitro potential to inhibit T-cell function via secretion of soluble mediators, such as prostaglandin E 2 . 16,36 However, MSCs potentiate fibrotic differentiation of other mesenchymal cells by secreting profibrotic mediators, such as TGF-␤1. 37 Thus, although MSCs can likely modulate an inflammatory microenvironment, they can also promote fibrogenesis by secreting profibrotic mediators 37 or differentiating to myofibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Surface marker expression for cells used in the present study was determined using flow cytometry. LR-MSCs were negative for CD45 and positive for CD73, CD105, CD90, and CD44.…”
Section: Isolation Of Lung-derived Mscs and Other Cell Linesmentioning
confidence: 99%
“…Moreover, MSCs show multipotent stem 41 cell characteristics [2] and special immunological features [3]. MSCs 42 can also be obtained from various tissues including peripheral blood, 43 umbilical cord, placenta, vein wall, muscle, adipose and connective 44 tissues [4].…”
mentioning
confidence: 99%
“…These data, would support the idea that IL10 gives a relevant contribution to the inhibiting activity present in BMSC-PBMC cocultures, besides the reported role of PGE2 in BMSC-and/or fibroblast-like-mediated immunosuppression. 9,14,36 It has been recently reported that BMSC can support Bcell survival by delivering anti-apoptotic and pro-differentiating signals. 19 We found that fluvastatin can significantly inhibit the pro-survival signal delivered by BMSC to B cells in the presence of dexamethasone, although this signal is marginally inhibited in the absence of corticosteroids.…”
Section: Discussionmentioning
confidence: 99%